FLOOD VULNERABILITY BASED ON SOCIAL ECONOMY CONDITION AT FLOOD PRONE AREA IN PURWOREJO REGENCY, CENTRAL JAVA, INDONESIA - , Nugroho Fajar Ariyanto, Ir. Suryanto, MSP ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Based on geomorphology aspect, some areas in Purworejo Regency are categorized as flood prone areas. One of them is Butuh District which is categorized as high flood prone area. Flood occurs almost every year in this area and results losses to the community. There are four type of vulnerability on community level